Migrant and ethnic inequalities in cervical cancer screening: exploring the role of cultural health capital using data from the Belgian Health Interview Survey - Sarah Derveeuw; Katrien Vanthomme; Sara Willems; Sorana Toma (BMC Public Health)
Abstract Background Preventive cancer screenings improve health outcomes, yet inequalities in access to and engagement with cervical cancer screening persist among minoritised populations, particularly migrants and ethnically minoritised groups. This study examines whether inequalities in the accumulation of health-related cultural resources (knowledge, values, and skills that individuals can use to promote their health) help explain ethnic disparities in cervical cancer screening within a European context, drawing on the theoretical concept of “cultural health capital”. Methods Using data from the 2013 and 2018 Belgian Health Interview Surveys (n = 6,247), we employed logistic regression models to explore the relationships among migrant background, cultural health capital (reflecting primary prevention, secondary prevention and healthcare provider engagement), and cervical cancer screening participation, controlling for socioeconomic and health factors. Results We identified persistent migrant and ethnic disparities in screening, even after adjusting for socioeconomic and cultural health capital factors. Although cultural health capital accumulation patterns varied considerably across migrant backgrounds and were consistently linked to increased cervical cancer screening uptake, these associations did not fully account for the observed inequalities. Notably, first-generation non-European migrants gained fewer benefits from higher cultural health capital. Conclusions Our results highlight the importance of considering intersecting factors such as length of residence, racialisation and ethnicization, in shaping cultural health capital accumulation. While cultural health capital correlates positively with cervical cancer screening uptake for most groups, it does not fully explain the observed disparities, underscoring the role of systemic barriers in perpetuating inequalities. Future studies should refine cultural health capital measurement and investigate the barriers that diverse populations encounter in their cultural health capital accumulation process.